Analisis Total Quality Management dengan RCA dan FMEA pada Puskesmas XYZ, Indramayu - Anggraeni, Anggraeni; Fety Nurlia Muzayanah (Yayasan Literasi Sains Indonesia, 2025)
This study aims to determine the implementation of Total Quality Management (TQM) in the XYZ Health Center using 10 TQM Elements according to Goetsch and Davis, as well as using the Root Cause Analysis (RCA) method to determine the main causes of existing problems regarding quality and Failure Mode and Effect Analysis (FMEA) analysis to determine improvements that need to be prioritized. The method used is a mix method, namely qualitative and quantitative. Data collection method by triangulation of sources, techniques and time. The results of this study show that the XYZ Health Center has implemented several efforts in the TQM element but it is still not optimal both in terms of implementation and results. Analysis with RCA with Fishbone diagram found that problems occurred in Cluster 3 on human factors, methods or procedures, machines and materials. Problems with the method factor are the most common problems. Meanwhile, the analysis with FMEA obtained three failure modes with the highest RPN (Risk Priority Number) to be given recommendations for improvement. The mode of failure is that the patient does not understand the information provided regarding the service rules, the patient is not honest about the health condition and the patient does not carry a personal identity.